Random nonlinear vibration of wagon - Duc, Kieu The (Vietnam Journal of Mechanics, 1993)
In this paper, the random nonlinear vibration of wagon in the model of two degrees of freedom is examined. Two kinds of nonlinear wagon have been considered: wagon with nonlinear spring and wagon with nonlinear damping force. The results are obtained by averaging method and FPK equations one.